The determinants of participation in microfinance and its impact on rural welfare: case study of the National Development Bank Botswana's Temo Bokamoso Lending programme in Kweneng District - Bayen Bayen, Edmund (Research of GSB, 2018)
This thesis investigates the determinants of participation in microfinance programmes and its impact on rural welfare in order to suggest improvements to the level of participation and the effectiveness of the programmes. The level of participation by rural smallholders in Botswana is much lower than expected in spite of the availability of schemes and their ease of access. The study uses one of National Development Bank Botswana's credit schemes in Kweneng District to investigate this problem. A field survey was carried out on 112 smallholder farmers, half of whom are scheme participants, to establish what factors affect the probability of their participation in the scheme. The study applied a logit model to determine which variables significantly affected the probability of participation in the credit scheme. The results indicated that some variables like gender and educational status had little effect on the probability of participation. A number of policy variables which include age, previous experience of credit use, respondents' perception of group collateral, distance from the National Development Bank, access to irrigation and total landholding size were found to have a significant effect. On the welfare effect, more than half of participants in the microfinance credit scheme indicated that their welfare improved as a direct result of the programme. As future research, it would be useful if the study could be extended to all districts of the country to enable the generalization of findings and provide valuable information for agricultural and poverty alleviation policy purposes.